Atypical Presentation of Vulval Tuberculosis (Bangladesh Medical Journal, 2009)
A 25yrs old lactating women present with membranous lesion of the tongue, painful ulceration of mouth and vulva. The differential diagnosis of vulval ulcer includes various causes of acute vulval lesion usually associated with STD, malignancy and immunosuppressive disease. Later it is diagnosed as a case of vulval tuberculosis. This common lesion is often misdiagnosed, leading unnecessary investigations and treatment.   DOI: 10.3329/bmj.v38i2.3577 Bangladesh Medical Journal 38(2) 2009 65-67